Advantages of jelly over liquid formulations for pediatrics - Doolaanea, Abd Almonem; Bahari, AZBS (2017)
Jellies for oral administration are non-flowable gelatinous preparations having a certain shape and size. This dosage form is being explored for applications for pediatric patients and other populations like geriatric and dysphagic patients. It has several advantages over liquid dosage forms in term of palatability, patient acceptance, suitability for controlled release applications and stability. Due to lack of information of several aspects of jellies for pediatrics, much more further studies are encouraged